Métodos de bloqueio por oscilações de potência: uma análise em linhas de transmissão de três terminais - Veiga, Matheus Fanfa da (2022)
The disturbances resulting from power swing (OP) cause, in a harmful way to the electrical power system (SEP), acceleration or delay in the rotor angle between synchronous generators in relation to synchronous frequency, in addition to variation between load balancing and generation. The consequences of the OP phenomenon at the transmission line terminals (LTs) are fundamentally instabilities in voltage and current values, exposing the distance protection (ANSI 21) to incorrect actions and, consequently, causing a possible blackout. Thus, in order to inhibit undue occurrences of the ANSI 21 distance function, the detection of the OP phenomenon, as well as actuation, is corroborated through the blocking function (ANSI 68). Three-terminal lines are often a cost-saving option in planning, as there is a reduction in the cost associated with having to build a substation at the connection point. However, the complexity and challenge in the elaboration of protection projects, especially distance protection, increases. Therefore, with the purpose of analyzing the occurrence of the OP phenomenon, as well as promoting the development of algorithm tests of functions 21 and 68 in three-terminal lines, the characterization of the main quantities that are affected during oscillations were applied in the present work. of potency. For the recognition and verification of the generated signals and, therefore, the decision making for the blocking function (ANSI 68), the algorithms of three methods were implemented, Concentric Characteristics Method (MCC), Double Blinder Method (MDB) and Electric Center Voltage Variation Method (MVTCE), which are compared. The implementation of the methods was carried out in MATLAB® and simulation of the cases in SIMULINK. The results obtained show that the methods for OP blocking, when applied to three-terminal lines, present failures, especially when the three terminals have sources, therefore, they cannot be applied to this type of line.